Artemisia verlotiorum (Asteraceae) in the continental part of Ukraine: now in Kyiv - Mosyakin, S.L.; Boiko, G.V.; Glukhova, S.A. (Український ботанічний журнал, 2019)
Colonies of Artemisia verlotiorum (Asteraceae), an alien species of East Asian origin now widespread in many countries
of the world, were found in 2018 in Kyiv in the Syrets Arboretum (Syretskiy Dendropark) and in a nearby abandoned plant nursery
and greenhouses. At present, three clonal colonies have been revealed. Most probably rhizomes of that species were initially
introduced to Kyiv with soil and/or imported trees and/or shrubs. However, one colony (along the wall of the administrative
building of the arboretum) most probably emerged from seeds dispersed by wind from the main (supposedly initial) colony in the
abandoned nursery. Before our find in Kyiv, A. verlotiorum was reliably known in Ukraine in Crimea (reported since the 1920s),
Transcarpathia, and from Lviv (recent records, to be discussed in detail in a forthcoming article). Most probably A. verlotiorum is
spreading in Eastern Europe mainly by rhizome fragments with soil and plant material. Other alien taxa of the Artemisia vulgaris
group (especially A. umbrosa and A. argyi) occur in Ukraine mainly as "railroad" plants. Колонії Artemisia verlotiorum (Asteraceae), виду східноазійського походження, нині натуралізованого у багатьох країнах світу, були знайдені у 2018 році в Києві у Сирецькому дендропарку, а також неподалік нього на території покинутого розплідника рослин і біля теплиць. Виявлені три клональні колонії. Найімовірніше кореневища рослин цього виду спочатку були завезені у Київ з ґрунтом або імпортованими деревами та кущами. Однак одна колонія (уздовж стіни адміністративної будівлі дендропарку), вірогідно, виникла з насіння, занесеного вітром з головної (ймовірно первинної) колонії у розпліднику. До нашої знахідки у Києві вид А. verlotiorum був достовірно відомий в Україні з Криму (наводився з 1920-х рр.), Закарпаття та Львова (дані детальніше обговорюватимуться у наступній статті). Найбільш ймовірно, що A. verlotiorum поширюється у Східній Європі переважно фрагментами кореневищ та/ або столонів з ґрунтом і рослинним матеріалом. Інші адвентивні види групи Artemisia vulgaris (особливо A. umbrosa і A. argyi) трапляються в Україні переважно як "залізничні" рослини.